Significance of chlorine‐dioxide‐based oral rinses in preventing SARS‐CoV‐2 cell entry. (28th July 2022) - Travis, Briana Joy; Elste, James; Gao, Feng; Joo, Bo Young; Cuevas‐Nunez, Maria; Kohlmeir, Ellen; Tiwari, Vaibhav; Mitchell, John C.
Abstract: Objective: This work aims to determine the efficacy of preprocedural oral rinsing with chlorine dioxide solutions to minimize the risk of coronavirus disease 2019 (COVID‐19) transmission during high‐risk dental procedures. Methods: The antiviral activity of chlorine‐dioxide‐based oral rinse (OR) solutions was tested by pre‐incubating with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pseudovirus in a dosage‐dependent manner before transducing to human embryonic kidney epithelial (HEK293T‐ACE2) cells, which stably expresses ACE‐2 receptor. Viral entry was determined by measuring luciferase activity using a luminescence microplate reader. In the cell‐to‐cell fusion assay, effector Chinese hamster ovary (CHO‐K1) cells co‐expressing spike glycoprotein of SARS‐CoV‐2 and T7 RNA polymerase were pre‐incubated with the ORs before co‐culturing with the target CHO‐K1 cells co‐expressing human ACE2 receptor and luciferase gene. The luciferase signal was quantified 24 h after mixing the cells. Surface expression of SARS‐CoV‐2 spike glycoprotein and ACE‐2 receptor was confirmed using direct fluorescent imaging and quantitative cell‐ELISA. Finally, dosage‐dependent cytotoxic effects of ORs were evaluated at two different time points. Results: A dosage‐dependent antiviral effect of the ORs was observed against SARS‐CoV‐2 cell entry and spike glycoprotein mediated cell‐to‐cell fusion. This demonstrates that ORs can be useful as a preprocedural step to reduce viral infectivity. Conclusions: Chlorine‐dioxide‐based ORs have a potential benefit for reducing SARS‐CoV‐2 entry and spread.